2020
DOI: 10.1101/2020.11.18.20230375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicenter evaluation of the Panbio™ COVID-19 Rapid Antigen-Detection Test for the diagnosis of SARS-CoV-2 infection

Abstract: The standard RT-PCR assay for COVID-19 is laborious and time-consuming, limiting the availability of testing. Rapid antigen-detection tests are faster and less expensive; however, the reliability of these tests must be validated before they can be used widely. The objective of this study was to determine the reliability of the PanbioTM COVID-19 Ag Rapid Test Device (PanbioRT) (Abbott) for SARS-CoV-2 in nasopharyngeal swab specimens. This was a prospective multicenter study in ten Spanish university hospitals o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
5
12
0
Order By: Relevance
“…In our study, the overall specificity of the antigen test was found to be very high (99.9 %). This is consistent with previous reports, which all showed specificity numbers close to 100 % ( [6] , [7] , [8] , [9] , [10] , [11] , [12] ). False positive results are thus rare.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our study, the overall specificity of the antigen test was found to be very high (99.9 %). This is consistent with previous reports, which all showed specificity numbers close to 100 % ( [6] , [7] , [8] , [9] , [10] , [11] , [12] ). False positive results are thus rare.…”
Section: Discussionsupporting
confidence: 94%
“…In the samples with ct values below 30, we found the RAT’s sensitivity to be 83.8 %. This is in line with previous studies which also found an association between high viral load (ct values < 30 or viral load > 10 6 copies/ml) and increased sensitivity, with reports ranging from 80.0 % to 98.0 % ( [6] , [7] , [8] , [9] , [10] , [11] , [12] ). This indicates that the majority of infectious cases can be correctly identified with the RAT.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations